Salmonella serotypeTyphi, Shigella, and intestinal parasites among food handlers at Bahir Dar University, Ethiopia - Abera, Bayeh; Yitayew, Gashaw; Amare, Hiwot (The Journal of Infection in Developing Countries, 2016)
Introduction:Food handlers play a major role in the transmission of Salmonella serotype Typhi (S. Typhi), Shigella, and intestinal parasites. This study was conducted to determine the prevalence of S. Typhi, Shigella, and intestinal parasites among food handlers at Bahir Dar University, Ethiopia. Methodology: A cross-sectional study was conducted in June 2014. Stool samples from 410 food handlers were examined for bacterial pathogens and parasites. Pearson’s Chi-square test, Fisher’s exact test, and bivariate and multivariate logistic regression analyses were used where appropriate. Results: The prevalence of S. Typhi, Shigella, and intestinal parasites among food handlers was 11 (2.7%), 5 (1.2%), and 53 (12.9%), respectively. Among eight intestinal parasites identified, the two most prevalent intestinal parasites were hookworm 26 (6.3%) and G. lamblia 13 (3.1%). Male food handlers were more likely to be positive than were female food handlers for S. Typhi and intestinal parasites. Furthermore, food handlers who had a history of regular medical checkups were less infected with intestinal parasites. Being male (AOR: 2.1, 95% CI: 1.2, 4.4) and not attending medical checkups (AOR: 2.9, 95% CI: 1.4, 6.1) were independent predictors of intestinal parasitic infection in food handlers. Male food handlers were reluctant to have regular parasitological examinations. Conclusions: There was a high proportion of food handlers with S. Typhi, Shigella, and intestinal parasites in their faces. Special emphasis should be placed on S. Typhicarriers and male food handlers. Education and periodical medical checkups for intestinal parasites and S. Typhi should be considered as intervention measures.